TSG-6 Is Involved in Fibrous Structural Remodeling after the Injection of Adipose-derived Stem Cells - Kiuchi, Satomi; Lopes, Tiago J.S.; Oishi, Takaya; Cho, Yuki; Ochiai, Hiroko; Gomi, Takamasa (Plastic and reconstructive surgery. Global open, 2024)
Background: Although aesthetic treatments can rejuvenate the skin, they often cause specific forms of tissue damage. Unlike wounding, which typically results in fibrotic scar tissue, damage from aesthetic treatments induces a distinct histological rejuvenation. The mechanisms that drive this rejuvenation are not yet fully understood. Here, we were interested in cellular responses following aesthetic treatments injecting adipose-derived stem cells (ASCs) subcutaneously. Through investigation with an ex vivo experimental model, a key gene was identified that orchestrates fibrous structural changes and tissue remodeling. Methods: Using fresh human subcutaneous adipose tissue co-cultured with ASCs, the changes in the fibrous architecture of the tissue were sequentially mapped. The key regulatory genes involved in remodeling were identified using gene expression and computational analyses. Results: We identified the regulatory elements that are crucial for tissue remodeling. Among those, we found that tumor necrosis factor-stimulated gene-6 (TSG-6) is a paracrine mediator essential for the collagen activity. It not only alleviates tissue inflammation but also promotes collagen replacement ex vivo. This is primarily achieved by inhibiting the formation of neutrophil extracellular traps, which are known to promote fibrosis. Conclusions: TSG-6 is a key factor modulating tissue inflammation. As our results demonstrate, after ASCs treatment, this factor directs skin healing away from fibrosis by reducing neutrophil extracellular trap formation in subcutaneous adipose tissue and promotes fibrous rejuvenation.